2022
DOI: 10.5483/bmbrep.2022.55.7.040
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitoNEET induces Pink1-Parkin-mediated mitophagy

Abstract: MitoNEET, a mitochondrial outer membrane protein containing the Asn-Glu-Glu-Thr (NEET) sequence, controls the formation of intermitochondrial junctions and confers autophagy resistance. Moreover, mitoNEET as a mitochondrial substrate undergoes ubiquitination by activated Parkin during the initiation of mitophagy. Therefore, mitoNEET is linked to the regulation of autophagy and mitophagy. Mitophagy is the selective removal of the damaged or unnecessary mitochondria, which is crucial to sustaining mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…We have shown that depletion of CISD proteins increased mitophagy in vivo and in human cells. A recent report has also described that genetic or pharmacologic inhibition of CISD1 upregulated Parkin-dependent mitophagy in human cells [55], although our data indicate that Cisd depletion-induced mitophagy can be Parkin-independent since it occurred in parkin mutant ies. Interestingly, while we found that Cisd depletion-induced mitophagy alleviated blocked mitochondrial turnover in Pink1/parkin mutants, under steady-state conditions mitophagy induction occurred in quite selective circumstances, notably in aged muscle.…”
Section: Discussioncontrasting
confidence: 74%
“…We have shown that depletion of CISD proteins increased mitophagy in vivo and in human cells. A recent report has also described that genetic or pharmacologic inhibition of CISD1 upregulated Parkin-dependent mitophagy in human cells [55], although our data indicate that Cisd depletion-induced mitophagy can be Parkin-independent since it occurred in parkin mutant ies. Interestingly, while we found that Cisd depletion-induced mitophagy alleviated blocked mitochondrial turnover in Pink1/parkin mutants, under steady-state conditions mitophagy induction occurred in quite selective circumstances, notably in aged muscle.…”
Section: Discussioncontrasting
confidence: 74%
“…Mdivi‐1, an inhibitor of Drp1, was reported in studies to block mitochondrial fission. CCCP and Mdivi‐1 have been reported in several studies as regulators of mitophagy 25,26,28 . Next, we focused on the relationship between mitochondria and intracellular parasitism of S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…CCCP and Mdivi‐1 have been reported in several studies as regulators of mitophagy. 25 , 26 , 28 Next, we focused on the relationship between mitochondria and intracellular parasitism of S. aureus . CCCP and Mdivi‐1 were used to regulate mitochondrial autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…NL-1 has shown promise in mouse models of traumatic brain injury (Yonutas et al , 2020), ischemic stroke (Saralkar et al , 2021), and lipopolysaccharide-induced inflammation (Lee et al , 2022b). It was even shown to induce mitophagy by promoting accumulation of PINK1 and Parkin (Lee et al , 2022a). Future studies will further explore the potential of NL-1 to mitigate the progression of Parkinson’s disease in animal models and potentially in patients.…”
Section: Discussionmentioning
confidence: 99%